Mode i stress intensity factors of slanted cracks - Ismail, Al Emran; Awang, M.K.; Mohd Tobi, A.; Ahmad, M.H. (Asian Research Publishing Network (ARPN), 2017)
The solutions of stress intensity factors of slanted cracks in plain strain plate are hard to find in open literature. There are some previous solutions of stress intensity factors available, however they are not studied completed except for the case of plain stress. The slanted cracks are modelled numerically using ANSYS finite element program. There are ten slanted angles and seven relative crack depths are used and the plate containing cracks is assumed to fulfil the plain strain condition. The plate is then forced uni-axially the stress intensity factors are determined according to the displacement extrapolation method. Based on the numerical analysis, it is found that slanted angles have inverse effects on the behaviour of stress intensity factors. Increasing such angles capable to reduce the mode I stress intensity factors. On the other hand, it is also enhanced the capability of mode II stress intensity factors at the crack tip. Due to difficulty of determining stress intensity factors numerically, a regression technique is used to formulate mathematical expressions which are capable to predict the stress intensity factors in reasonable accuracies.